PEMENUHAN HAK-HAK KONSUMEN PENGGUNA JASA ANGKUTAN UMUM BUS TRANS METRO PEKANBARU OLEH PENGELOLA BUS TRANS METRO PEKANBARU - R, Arnoldus Daniel; ', Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Steps to enhance the dignity and consciousness of the consumer must begin withan attempt to understand the fundamental rights of consumers, which can serve as the basisfor the struggle to realize those rights. In general there are 4 basic rights of consumers,namely the right to obtain security, the right to obtain information, the right to vote, the rightto be heard. Based on this understanding, the authors formulate two problems, namely: First,What is the legal relationship between Consumer users of public transit bus service TransMetro Pekanbaru with Trans Metro bus management Pekanbaru ?, Secondly, Whetherconsumers harmed their rights can sue to the Trans Trans bus Pekanbaru ?.The type of research used by the author is empirical law research or alsoknown as sociological law research, that is research conducted by how toeffectiveness of law apply in society. Kegitan done in collecting data in this researchis document study or library materials. This document or library study includes aquestionnaire.From the results of research there are several problems that can besummarized as follows: First, the emergence of legal relations if the occurrence ofacts against the law. Secondly, the public transportation service user of Bus TransMetro Pekanbaru can provide Criticism and suggestion related to the facility throughthe phone number of complaint in Trans Metro bus Pekanbaru or come directly toCity Transportation Office of Pekanbaru. Third, But the community can notcomplain. Because this is a public facility. Not all people's wishes can be fulfilled.Keywords: Consumer Protection-Trans Metro Bus Pekanbaru.